2015
DOI: 10.1038/srep13212
|View full text |Cite
|
Sign up to set email alerts
|

The stool microbiota of insulin resistant women with recent gestational diabetes, a high risk group for type 2 diabetes

Abstract: The gut microbiota has been linked to metabolic diseases. However, information on the microbiome of young adults at risk for type 2 diabetes (T2D) is lacking. The aim of this cross-sectional analysis was to investigate whether insulin resistant women with previous gestational diabetes (pGDM), a high risk group for T2D, differ in their stool microbiota from women after a normoglycemic pregnancy (controls). Bacterial communities were analyzed by high-throughput 16S rRNA gene sequencing using fecal samples from 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
102
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 48 publications
6
102
2
Order By: Relevance
“…Previous research has linked this group to CVD risk factors including obesity 35, 36 and diabetes 3739 , but the directions of reported associations have been inconsistent. For example, Furet and colleagues identified a decreased frequency of the Prevotella group in obese versus non-obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has linked this group to CVD risk factors including obesity 35, 36 and diabetes 3739 , but the directions of reported associations have been inconsistent. For example, Furet and colleagues identified a decreased frequency of the Prevotella group in obese versus non-obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…When members of both families co-occur in the gut, one or the other predominates because they have an antagonistic relationship (29). In fact, an inverse association between Bacteroidetes and Prevotella has been reported with obesity and type 2 diabetes in nonpregnant individuals (30,31) and now in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Others found that the placental microbiota and microbiome differed between women with and without gestational diabetes 117. The stool microbiota of insulin resistant women with a history of gestational diabetes has been characterized postpartum, and women with former gestational diabetes had relatively higher abundance of the Prevotellaceae family as well as reduced abundance of Firmicutes, similar to the situation in type 2 diabetes 118. Another cross sectional study of the gut microbiome in women who had gestational diabetes and their offspring five years postpartum found no significant differences in gut microbiota between women who had gestational diabetes and controls, but some differences existed between offspring of women who had gestational diabetes and those who did not 119…”
Section: Emerging Treatmentsmentioning
confidence: 99%